2000-year-old pathogen genomes reconstructed from metagenomic analysis of Egyptian mummified individuals - Judith Neukamm; Saskia Pfrengle; Martyna Molak; Alexander Seitz; Michael Francken; Partick Eppenberger; Charlotte Avanzi; Ella Reiter; Christian Urban; Beatrix Welte; Philipp W. Stockhammer; Barbara Teßmann; et al. (BMC Biology, 2020)
Abstract Background Recent advances in sequencing have facilitated large-scale analyses of the metagenomic composition of different samples, including the environmental microbiome of air, water, and soil, as well as the microbiome of living humans and other animals. Analyses of the microbiome of ancient human samples may provide insights into human health and disease, as well as pathogen evolution, but the field is still in its very early stages and considered highly challenging. Results The metagenomic and pathogen content of Egyptian mummified individuals from different time periods was investigated via genetic analysis of the microbial composition of various tissues. The analysis of the dental calculus’ microbiome identified Red Complex bacteria, which are correlated with periodontal diseases. From bone and soft tissue, genomes of two ancient pathogens, a 2200-year-old Mycobacterium leprae strain and a 2000-year-old human hepatitis B virus, were successfully reconstructed. Conclusions The results show the reliability of metagenomic studies on Egyptian mummified individuals and the potential to use them as a source for the extraction of ancient pathogen DNA.